Tick-borne Encephalitis Virus in Arthropod Vectors in the Far East of Russia - Pukhovskaya, Natalia M.; Morozova, Olga V.; Vysochina, Nelya P.; Belozerova, Nadejda B.; Bakhmetyeva, Svetlana V.; Zdanovskaya, Nina I.; Seligman, Stephen J.; Ivanov, Leonid I. (Ticks and Tick-borne Diseases, 2018)
Isolates of tick-borne encephalitis virus (TBEV) from arthropod vectors (ticks and mosquitoes) in the Amur, the Jewish Autonomous and the Sakhalin regions as well as on the Khabarovsk territory of the Far East of Russia were studied. Different proportions of four main tick species of the family Ixodidae: Ixodes persulcatus P. Schulze, 1930; Haemaphysalis concinna Koch, 1844; Haemaphysalis japonica douglasi Nuttall et Warburton, 1915 and Dermacentor silvarum Olenev, 1932 were found in forests and near settlements. RT-PCR of TBEV RNA in adult ticks collected from vegetation in 1999-2014 revealed average infection rates of 7.9+/-0.7% in I. persulcatus, of 5.6+/-1.0% in H. concinna, of 2.0+/-2.0% in H. japonica, and of 1.3+/-1.3% in D. silvarum. Viral loads varied in a range from 10(2) to 10(9) TBEV genome-equivalents per a tick with the maximal values in I. persulcatus and H. japonica. Molecular typing using reverse transcription with subsequent real time PCR with subtype-specific fluorescent probes demonstrated that the Far Eastern (FE) subtype of TBEV predominated both in mono-infections and in mixed infection with the Siberian (Sib) subtype in I. persulcatus pools. TBEV strains of the FE subtype were isolated from I. persulcatus, H. concinna and from a pool of Aedes vexans mosquitoes. Ten TBEV strains isolated from I. persulcatus from the Khabarovsk territory and the Jewish Autonomous region between 1985 and 2013 cluster with the TBEV vaccine strain Sofjin of the FE subtype isolated from human brain in 1937. A TBEV strain from H. concinna collected in the Amur region (GenBank accession number KF880803) is similar to the vaccine strain 205 isolated in 1973 from I. persulcatus collected in the Jewish Autonomous region. The TBEV strain Lazo MP36 of the FE subtype isolated from a pool of A. vexans in the Khabarovsk territory in 2014 (KT001073) differs from strains isolated from 1) I. persulcatus (including the vaccine strain 205) and H. concinna; 2) mosquitoes [strain Malishevo (KJ744034) isolated in 1978 from Aedes ...